On Jensen's inequality for the power function of norm of bounded linear operators. (October 2019) - Li, Zheng; Zhang, Tie; Li, Changjun
Abstract: Some Jensen's inequalities for the power function of norm of bounded linear operators are proposed. First, a Jensen's inequality for a power function on ℝ is investigated. Based on it, Jensen's inequality for the power function of norm of bounded linear operators is established. Finally, the discussion extends to the polynomial with non-negative coefficients of the power function of the norm, and corresponding Jensen's inequality is obtained.